(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the impact of empirical antibiotic therapy on diabetic foot infection. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at the Department of Surgery, Central Park Teaching Hospital, Lahore from January 2023 to June 2023. Methods: This descriptive study was conducted at Central Park Hospital, Lahore. A total of 100 participants with diabetic foot infections were enrolled in this study after taking informed consent. Data was entered and analyzed by SPSS 26. Results: In this study the mean age of the cases was 45.12 ± 3.88 in group A and 46.72 ± 4.17 in group B. there were 31 (62%) males and 19 (38%) females were found in group A while 28 (56%) male and 22 (44%) female were found in group B. Among gram positive bacterias staphylococcus aureus was found most prevalent found in 51% patients. Among gram negative bacteria pseudomonas aeruginosa was found in 42% cases. The comparison of drug effectiveness showed sensitivity of linezolid 92% and vancomycin 90% with insignificant p-value 0.727 showing both drugs equally effective. Conclusion: Both vancomycin and linezolid are equally good but antibiotics should be timely administered to manage the diabetic foot and to prevent super imposed infection.